Risks and possibilities of the effect of financial inclusion on managing the financial security at the macro level - Nataliia Zachosova; Olena Herasymenko; Аnnа Shevchenko (Investment Management & Financial Innovations, 2018)
The financial security state of the country directly depends on the amount of resources available in the financial system. Internal sources of financing of the economic and social needs may deprive the government of the necessity seek opportunities for obtaining external borrowings, which lead the country to the loss of financial autonomy. The financial inclusion of the population and business entities into the process of using financial products and services will stabilize the situation in the financial market by obtaining additional financial resources by its professional participants. At the same time, the lack of control of this process can lead to new threats for financial security at micro and macro levels. In view of this, the purpose of the study is to specify the opportunities and risks of financial inclusion for the financial security of financial intermediaries and the state as a whole. The object of the study was the level of financial inclusion, a set of factors that affect it, and a list of the consequences that its change may have for financial security. As the theoretical basis of the study, the reporting materials of financial market regulators were used, as well as information obtained from the application of such methods of scientific research as the analysis by which the level of financial inclusion in different sectors of the financial market was established, and the expert method implemented through surveys and questionnaires. Its use enabled to get a quantitative assessment of the level of financial inclusion of the population and economic entities. As a result of the study, the possible, positive consequences, risks and challenges of financial inclusion for the financial component of economic security are specified and systematized. The practical significance of the results of the survey is the possibility of developing on their basis the mechanisms for stimulating and controlling the level of financial inclusion by the financial market national regulators.